Encapsulated healing agents for asphalt self-healing - Al-Mansoori, Tariq Hussein Abees (2018)
Service life of asphalt roads could be extended by enhancing the natural self-healing ability of asphalt mixtures with encapsulated rejuvenators. When crack damage appears, the capsules release healing agents, which dissolve bitumen to flow into cracks. In this research, a new type of capsules was developed. These capsules contain sunflower oil as a rejuvenating agent. The size, morphology, mechanical strength and thermal stability of these capsules were investigated. The composition of the capsules, which nominally divides these capsules into different types based on their oil content, epoxy-cement shell and polymer amount, and its effect on capsule characteristics were also studied. In addition, the effect of the capsules on the chemical composition of bitumen with time of exposure to broken capsules was evaluated by the FTIR test. Results show that the characteristics of the capsules and their effect on chemical composition allow them to be incorporated in asphalt mixtures for further investigations for their effect on asphalt mechanical performance and self-healing. The mechanical performance of aged asphalt mixtures is investigated by using three nominally different types of capsules. Two of these were protected with a hard shell made of epoxy-cement composite; two coats with 1.0 o/w (oil-to-water), three coats with 1.0 o/w and without the hard shell with 0.5 o/w. The optimum amount of capsules used in all mixtures was 0.5% of total mass of asphalt mixture. Tests started by investigating the effect of mixing and compaction processes on these capsules. Results show that the hard shell (epoxy-cement) was not necessary for the capsules to survive mixing and compaction processes. Capsules deformed and broke with cyclic loading, releasing oil that diffused in the bitumen in less than 24h. Healing of cracks in aged asphalt mixtures led to an increase of stiffness under cyclic loading. However, asphalt specimens with capsules had lower deformation resistance. Computer tomography scanning of specimens showed large reductions in cracks around the capsules, after resting 4 days (96h) at 20ºC. The mechanical properties of asphalt mixture containing capsules have been evaluated. Including water sensitivity, particle loss, stiffness and permanent deformation. One type of capsule (0.1 o/w) with three different capsule contents by mass of asphalt mixture were used, 0.1%, 0.25% and 0.5% with oil-to-bitumen ratio 1.1, 2.8 and 5.5, respectively. Capsules were strongly bonded to the asphalt mixture and results showed improved or at least similar mechanical properties to that of asphalt mixtures without capsules. This shows that capsules for asphalt self-healing can be safely used in the road, without affecting its quality. Asphalt containing capsules had slightly lower stiffness (no rest period), which can be easily solved by reducing the size of the capsules in the future. Furthermore, a new method for testing asphalt self-healing by the action of capsules was designed and tested. This method was based on a 3-point bending test (3PB) to beak samples and measure their flexural strength. The test was implemented by comparing the strength recovery of the broken beams after healing to their original flexural strength. The test was first applied to asphalt mastic beams, which are asphalt mixtures with higher bitumen content and fine aggregate and filler. Five different types of capsules used, based on their o/w ratios. These were 0.05, 0.1, 0.2, 0.5 and 1.0 o/w ratios with different amounts depending on their oil content so that they can provide a 7.2% of rejuvenator (sunflower oil) to the asphalt mastic beams. The effect of capsule content on self-healing was investigated by the 3PB on samples containing all those five capsule types (different contents) at one healing temperature, namely 20oC and different healing times. Effect of temperature on healing was investigated as well by 3PB test applied to mastic beams containing one type of capsules with 0.5 o/w ratio at four different temperatures, namely 5oC, 10oC, 15oC and 20oC. The main results showed that the capsules can break inside the asphalt mastic releasing the encapsulated oil to bitumen. Healing levels in the asphalt mastic samples with capsules were greater than samples without capsules, and the healing level of asphalt samples with, and without, capsules increased with the healing time. Additionally, the healing level given by the capsules inside the cracked asphalt mastic depended on the oil/water content of the capsule and on the temperature at which the healing process occurs. Finally, a correlation factor was developed between the healing level of asphalt mastic with and without capsules, independent of the temperature and time evaluated. Self-healing of real asphalt mixture was also investigated by same method of 3PB at different healing times and different temperatures. One type of capsules, namely 0.1 o/w with three different capsule contents, 0.10%, 0.25% and 0.50% by total weight of the mixture, were mixed with the asphalt. Eight different healing temperatures were used in this test, namely -5oC, 5oC, 10oC, 15oC, 20oC, 30oC, 40oC and 50oC. It was proven that the capsules can resist the mixing and compaction processes and break inside the asphalt mixture as a result of applying external mechanical loads, releasing the encapsulated oil. The capsules content in asphalt mixture has a significant influence on the healing level, where a higher capsule content led to higher healing levels. It was found that cracked asphalt mixture with capsules recovered 52.9% of initial strength at 20ºC versus 14.0% of asphalt mixture without capsules. Likewise, asphalt with, and without, capsules presents an increase of the healing level when the temperature increases. Finally, it was proved that healing temperature over 40ºC has significant influence on the healing levels of the asphalt beams.